2010
DOI: 10.1073/pnas.0911427107
|View full text |Cite
|
Sign up to set email alerts
|

Hippo signaling is a potent in vivo growth and tumor suppressor pathway in the mammalian liver

Abstract: How organ size is controlled in mammals is not currently understood. In Drosophila the Hippo signaling pathway functions to suppress growth in imaginal discs and has been suggested to control organ size. To investigate the role of hippo signaling in regulation of mammalian organ size we have generated conditional alleles of Sav1 , mst1 , and mst2 , orthologs of Drosophila Salvador and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

32
643
1
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 656 publications
(678 citation statements)
references
References 39 publications
32
643
1
2
Order By: Relevance
“…Overexpression of TAZ has also been noted in human breast cancer samples and non-small cell lung cancer cell lines (Chan et al, 2008;Zhou et al, 2011b). Similar to YAP overexpression, ablation of the Hippo pathway components Mer and Sav and double knockout of Mst1/2 in mice result in liver enlargement and tumor formation characteristic of HCC and cholangiocarcinoma (CC) (Zhou et al, 2009;Benhamouche et al, 2010;Lee et al, 2010;Lu et al, 2010;Song et al, 2010;. Aberrant Mst1/2 and Lats1/2 expression is observed in human cancers (Hisaoka et al, 2002;Jimé-nez-Velasco et al, 2005;Takahashi et al, 2005;Jiang et al, 2006;Minoo et al, 2007;Seidel et al, 2007;Cho et al, 2009;Zhou et al, 2009).…”
Section: The Mammalian Hippo Pathwaymentioning
confidence: 95%
See 1 more Smart Citation
“…Overexpression of TAZ has also been noted in human breast cancer samples and non-small cell lung cancer cell lines (Chan et al, 2008;Zhou et al, 2011b). Similar to YAP overexpression, ablation of the Hippo pathway components Mer and Sav and double knockout of Mst1/2 in mice result in liver enlargement and tumor formation characteristic of HCC and cholangiocarcinoma (CC) (Zhou et al, 2009;Benhamouche et al, 2010;Lee et al, 2010;Lu et al, 2010;Song et al, 2010;. Aberrant Mst1/2 and Lats1/2 expression is observed in human cancers (Hisaoka et al, 2002;Jimé-nez-Velasco et al, 2005;Takahashi et al, 2005;Jiang et al, 2006;Minoo et al, 2007;Seidel et al, 2007;Cho et al, 2009;Zhou et al, 2009).…”
Section: The Mammalian Hippo Pathwaymentioning
confidence: 95%
“…It was first observed that intestinal-specific overexpression of YAP or knockout of Mst1/2 in mice caused marked expansion of the stem cell compartment (Camargo et al, 2007;Zhou et al, 2011a). Knockout of Hippo pathway components Mst1/2, Sav1, and Mer in liver also leads to accumulation of liver stem cells (Benhamouche et al, 2010;Lee et al, 2010;Lu et al, 2010;Song et al, 2010). The regulation of liver and intestinal stem cells by the Hippo pathway and its role in regeneration were discussed in great detail elsewhere (Chen et al, 2012).…”
Section: The Hippo Pathway Limits the Pool Of Tissue-specific Progenimentioning
confidence: 99%
“…We also found that HAX1 is up-regulated in breast cancer samples compared to normal breast tissues by searching the Oncomine database, and therefore it may also play an important role in breast cancer progression. Recently the Hippo signaling pathway was reported to be a critical regulator of mammalian liver growth and a potent suppressor of liver tumor formation (36). The mammalian Hippo-Salvador pathway restricts the proliferation of hepatic oval cells and thereby controls liver size and prevents the development of oval cell-derived tumors (37).…”
Section: Discussionmentioning
confidence: 99%
“…Of course, Drosophila offers an ideal model system for such studies: The wide range of genetic and genomic approaches available for use in flies has helped in elucidation of the mechanisms underlying determination of leg size and leg or wing disc regeneration (Bergantiñ os et al, 2010;Sun and Irvine, 2010). Recent evidence encouragingly suggests that the Wts-Hpo signaling pathway and Yki may act through the regulation of cell fate to control organ size in vertebrate systems (Dong et al, 2007;Lu et al, 2010;Pan, 2010;Zhao et al, 2010). Further work is needed, however, to identify the upstream signals and downstream master regulatory genes of the Ds-Ft signaling pathway in limb development and regeneration.…”
Section: Perspectivesmentioning
confidence: 99%